Impact of agroecological technologies on energy efficiency and greenhouse gas emission in a livestock system - Molina, Luis; Pinto, René; Guevara, Francisco; La O, Manuel; Raj, Deb; Berrones, Roberto (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
To mitigate greenhouse gas (GHG) emissions in the agricultural sector, it is necessary to propose alternatives based on a systemic vision and agroecological principles that allow for more efficient use of energy within the systems. The objective of this study was to evaluate three agroecological technologies by quantifying energy use and its relationship with GHG emissions and mitigation, to contribute to the sustainable management of a livestock system in Frailesca, Chiapas, Mexico. An ex-post facto study was conducted to establish five technological scenarios, based on combinations of the use of the three agroecological technologies, to calculate energy efficiency (EE) and estimate GHG, for which energy equivalences of the inputs and outputs of the production system were used. For the livestock system with conventional management, the energy efficiency was 0.63, generating a GHG emission of 93,153.96 kg of CO2eq in a period of six months; By incorporating combinations of the three agroecological technologies (compost, bio slurry and silvopastoral system) the energy efficiency increased to 0.82 and the GHG emission decreased to 71,523.63 kg of CO2eq. It is concluded that these agroecological technologies can be implemented in livestock systems in Chiapas, Mexico to contribute to the mitigation of GHG.